Mod Gud hjælper kun Gud - Nielsen, Kjeld Slot (Dansk Teologisk Tidsskrift, 2010)
Luther’s notion of deus absconditus in relation to deus revelatus has played a central role among Danish theologians such as Jakob Knudsen, K.E. Løgstrup, Ole Jensen and Jakob Wolf. But this emphasis on the hidden God raises difficulties in relation to God’s unity in general, and to the problem of God’s responsibility for evil in particular After dicussing two lines of Wolf’s interpretation of Løgstrup and a Trinitarian interpretation of Martin Wendte, a theological proposal is offered that integrates deus absconditus into God’s triune being, so that God’s responsibility for evil is maintained without threatening divine integrity.